Chest wall deformity found in patients with primary spontaneous pneumothorax. (October 2013) - Saita, Kosuke; Murakawa, Tomohiro; Kawano, Hirotaka; Sano, Atsushi; Nagayama, Kazuhiro; Nakajima, Jun
Background: the current consensus is that primary spontaneous pneumothorax frequently occurs in young male patients who are tall and thin. However, upon careful observation, many chest wall deformities have been recognized in primary spontaneous pneumothorax patients. We investigated the distinctive features of the chest wall configuration of primary spontaneous pneumothorax patients by comparing them with controls (normal and Marfan syndrome patients). Methods: the anteroposterior and transverse diameters of the bilateral hemithoraxes of each patient at predetermined levels were measured by computed tomography. The asymmetry, which was based on the right/left anteroposterior and right/left transverse diameter ratio, and thickness based on the anteroposterior/transverse ratio, were examined. Results: severe anteroposterior asymmetry and transverse asymmetry were observed in Marfan syndrome patients, and moderate anteroposterior asymmetry and transverse asymmetry were observed in primary spontaneous pneumothorax patients in comparison with normal control patients. Primary spontaneous pneumothorax and Marfan patients showed flatter thoraxes than normal control patients. Conclusions: primary spontaneous pneumothorax patients tend to have asymmetric and flat thoraxes. Subclinical thoracic wall deformity observed in the primary spontaneous pneumothorax group may partly contribute to alveolar pressure heterogeneity, and may be related to subpleural bleb formation.